1999
DOI: 10.1088/0953-4075/32/22/303
|View full text |Cite
|
Sign up to set email alerts
|

The dissociative recombination of NO+: the influence of the vibrational excitation state

Abstract: The dissociative recombination rate coefficient for NO+ has been measured at 300 K using a flowing afterglow Langmuir probe-mass spectrometer apparatus. A value of (4±1) × 10-7 cm3 s-1 has been found for ground electronic and vibrational state ions produced from the parent NO gas. Ions produced from a N2:O2 mixture which are in a wide range of vibrationally excited states display a smaller recombination rate of (1.6±0.5) × 10-7 cm3 s-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…Starting from the measured cross sections, the thermal (300 K) rate was calculated by numerical integration. In the second experiment, a flowing afterglow Langmuir probe-mass apparatus (Mostefaoui et al 1999) was used, with NO as parent gas; justifying the assumption that NO + is almost entirely in its ground vibrational state. The rate coefficient derived at T = 300 K are identical, within the error bar, for the two experiments: ((4 ± 1) × 10 −7 cm 3 /s and 4 × 10 −7 cm 3 /s respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from the measured cross sections, the thermal (300 K) rate was calculated by numerical integration. In the second experiment, a flowing afterglow Langmuir probe-mass apparatus (Mostefaoui et al 1999) was used, with NO as parent gas; justifying the assumption that NO + is almost entirely in its ground vibrational state. The rate coefficient derived at T = 300 K are identical, within the error bar, for the two experiments: ((4 ± 1) × 10 −7 cm 3 /s and 4 × 10 −7 cm 3 /s respectively.…”
Section: Resultsmentioning
confidence: 99%
“…64 For NO ϩ , the measured thermal rate of vibrationally excited ions is also reported to be lower than that of vibrational ground-state ions. 65 In the case of N 2 ϩ an experiment performed at CRYRING reported a weakly dependent total rate coefficient, where the rate of the vibrationally excited beam was again lower than that of the ground state. 66 In this paper there is also mention of the branching fractions of the vϭ1 -3 vibrational levels being roughly the same.…”
Section: A O 2 ¿ and Similar Systemsmentioning
confidence: 99%
“…The two other experimental techniques we consider here are the flowing afterglow Langmuir probe (FALP) technique (e.g., Mostefaoui et al, 1999) and the multipass merged beams technique (e.g., Le Padellec et al, 1999). Of importance for this study is the fact that ions in their ground electronic and vibrational states are most easily obtained in FALP experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Each species must be dealt with on an individual basis. For instance, it has been observed that the DR cross-sections decrease with increasing vibrational excitation for NO þ (e.g., Mostefaoui et al, 1999), while for H þ 2 , the cross-sections increase with increasing vibrational excitation (e.g., Hus et al, 1988).…”
Section: Introductionmentioning
confidence: 99%